2012
DOI: 10.3390/ijms131013049
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Optimization of a Palm-Based Nanoemulsion System Containing Levodopa

Abstract: Response surface methodology (RSM) was utilized to investigate the influence of the main emulsion composition; mixture of palm and medium-chain triglyceride (MCT) oil (6%–12% w/w), lecithin (1%–3% w/w), and Cremophor EL (0.5%–1.5% w/w) as well as the preparation method; addition rate (2–20 mL/min), on the physicochemical properties of palm-based nanoemulsions. The response variables were the three main emulsion properties; particle size, zeta potential and polydispersity index. Optimization of the four indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 27 publications
4
73
0
3
Order By: Relevance
“…Figure 9F and G shows that the combination of increased mixing rate and water content and the combination of increased mixing rate and addition rate widened the droplet-size distribution of the final emulsion. These results are well supported by previous reports 18,24 on high-pressure emulsification processes. Conversely, Figure 9D shows that the combination of increased water content and addition rate narrow droplet-size distribution.…”
Section: Polydispersity Indexsupporting
confidence: 82%
“…Figure 9F and G shows that the combination of increased mixing rate and water content and the combination of increased mixing rate and addition rate widened the droplet-size distribution of the final emulsion. These results are well supported by previous reports 18,24 on high-pressure emulsification processes. Conversely, Figure 9D shows that the combination of increased water content and addition rate narrow droplet-size distribution.…”
Section: Polydispersity Indexsupporting
confidence: 82%
“…Mathematical modeling offers a valuable tool for formulation optimization, by facilitating an integrated and quantitative assessment of the outcome of various formulation attributes on the response parameter(s) of interest, without the need to experimentally test each individual scenario. Studies by Zainol et al, illustrate the utility of the Response Surface Methodology in optimizing Levodopa Palm-based nanoemulsions (17): these authors were able to successfully predict the effects of varying the formulation composition and manufacturing process on three nanoemulsion variables: particle size, zeta potential and polydispersity index. Although this process is empirical, it nonetheless highlights the benefits of applying mathematical modeling to formulation optimization efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported the lipid nano-emulsions as a parenteral drug delivery device. These nano-emulsions can circulate in the blood for long period of time (Anuchapreeda et al, 2012) and minimize the pain by exposing the tissue to lower concentrations of drugs (Zainol et al, 2012). Furthermore, PKOEs with relatively shorter chain ester are potentially good for delivery of drug into the body (Keng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%